The Centrality of Conceptual Metaphor in Second Language Teaching and Learning | Markaziyyah al Isti’aroh Attashowuriyah Fii Ta’lim wa Ta’allum Allughah Atsaniyah - Ahmed Jaouhari; Muhammad Syaifullah (Mantiqu Tayr: Journal of Arabic Language, 2022)
This researchseeks to prove the pivotalrole of conceptual metaphor - as presented by the cognitive orientation launched by George Lakoffat the beginning of the eighties of the last century - in teaching and learning the second language, and how metaphor contributes to developing the cognitive abilities of learnersat the level of understanding and interpreting the speech of the second language, whetheritis oral or written. In order to clarify the interactions that exist between the metaphorical competence and the communicative competences of the learner, wedecided, since the beginning of this research, to identify some of the issues and hypotheses that metaphor stems from, highlighting the importance of metaphorical awareness in acquiring the target language, by linking the conceptual domain of the first language as a source domain with the conceptual domain of the second language as a target domain. In the context of this transition, we have high lighted the importance of conceptual fluencyas a contrast to linguistic fluence in the teaching and learning of the second language. Linguistic, social, textual, grammatical, strategic, and other educational competencies.